(2x)2 times (2x)2 = 16x4
(2x2) times (2x2) = 4x4
Chat with our AI personalities
Complete the square. X^2 + 2X halve the linear term ( 2 ), square it and add to polynomial X^2 + 2X + 1
8
(2x-5) (x-1)
Sqrt(24x4)/Sqrt(3x) = Sqrt(24x4/3x) = Sqrt(8x3) = Sqrt(4x2*2x) = 2x*sqrt(2x)
The square root of 8x can be simplified as √8x = √(4*2x) = 2√2x. This is because we can break down 8 into 4 and 2, and since the square root of 4 is 2, we can pull it out of the square root. Therefore, the simplified form of the square root of 8x is 2√2x.